2021
DOI: 10.1093/glycob/cwab096
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose-deficient Acinetobacter baumannii exhibits reduced virulence by losing capsular polysaccharide and altering membrane integrity

Abstract: A. baumannii has become the leading cause of bacterial nosocomial infections in part due to its ability to resist desiccation, disinfection and antibiotics. Several factors contribute to the tenacity and virulence of this pathogen, including production of a broad range of surface glycoconjugates, secretory systems and efflux pumps. We became interested in examining the importance of trehalose in A. baumannii after comparing intact bacterial cells by high resolution magic angle spinning NMR and noting high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…According to the metabolomic analysis, it was found that among the significantly upregulated compounds in S. ningpoensis honey (p-value ≤ 0.05 and VIP ≥ 1, Table S2), adenosine (C00212), chavicol (C16930), pyrimidodiazepine (C02587), trehalose (C01083), palmitoleic acid (C08362), linoleic acid (C04717), salidroside (C06046), D-xylitol (C00379) and perillyl alcohol (C02452) might contribute to its antibacterial function as they were reported to possess antimicrobial activity to different extents (Crippen et al, 2021;El-Kalyoubi et al, 2017;Figueiredo et al, 2020;Hossain et al, 2010;Jain et al, 2016;Li et al, 2018;Subramanian et al, 2019;Vitali et al, 2012). Furthermore, the KEGG analysis (Table S3 and Figure S6) revealed that some significantly variant compounds in S. ningpoensis honey were involved in the pathways associated with the antibacterial process.…”
Section: Discussionmentioning
confidence: 99%
“…According to the metabolomic analysis, it was found that among the significantly upregulated compounds in S. ningpoensis honey (p-value ≤ 0.05 and VIP ≥ 1, Table S2), adenosine (C00212), chavicol (C16930), pyrimidodiazepine (C02587), trehalose (C01083), palmitoleic acid (C08362), linoleic acid (C04717), salidroside (C06046), D-xylitol (C00379) and perillyl alcohol (C02452) might contribute to its antibacterial function as they were reported to possess antimicrobial activity to different extents (Crippen et al, 2021;El-Kalyoubi et al, 2017;Figueiredo et al, 2020;Hossain et al, 2010;Jain et al, 2016;Li et al, 2018;Subramanian et al, 2019;Vitali et al, 2012). Furthermore, the KEGG analysis (Table S3 and Figure S6) revealed that some significantly variant compounds in S. ningpoensis honey were involved in the pathways associated with the antibacterial process.…”
Section: Discussionmentioning
confidence: 99%
“…All three AMP treatments caused significant downregulation of trehalose-6-phosphate synthase encoded by the OtsA gene in A. baumannii, as identified by Iturriga et al in 2009 37 . Trehalose is utilised by A. baumannii as a stress protector in the event of salt and heat stress, and trehalose-6-phosphate is the precursor to this sugar molecule 38 . Trehalose-6-phosphate, in high quantities, is believed to be toxic to the bacterial cell and has been linked to growth inhibition and a reduction in tolerance to elevated heat and/or salt conditions 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Four biological replicates of the experiment were performed for each strain. Controls for the assay were performed using the Acinetobacter baumannii 5075 WT (robust survival) and A. baumannii 5075ΔpglC (complete killing)(Crippen et al, 2021). Saliva survival assay.…”
mentioning
confidence: 99%